Cover Crop Management in a Chardonnay/99 Richter Vineyard in the Coastal Region, South Africa. 3. Effect of Different Cover Crops and Cover Crop Management Practices on Organic Matter and Macro-nutrient Content of a Medium-textured Soil - Fourie, J.C.; Agenbag, G.A.; Louw, P.J.E. (South African Journal of Enology and Viticulture, 2016)
The trial was conducted over a period of 10 years (1993/94 to 2002/03) on a medium-textured soil in a Chardonnay/99 Richter vineyard near Stellenbosch (33°55’S, 18°52’E), which is situated in the Coastal wine grape region of the Western Cape, South Africa. Sixteen treatments, consisting of three cereals and five legumes, managed according to two cover crop management practices, were included. These treatments were compared to a control, in which no cover crop was sown and the weeds were controlled mechanically in the work row and chemically in the vine row from bud break to harvest (approximately the first week of February). A treatment in which no cover crop was sown and full-surface post-emergence chemical weed control was applied from before bud break to harvest (BB) (weedchem) was also included. After five seasons, the soil organic matter (SOM) content in the 0 to 300 mm soil layer increased in all the cover crop management treatments. In weedchem and in the control, SOM remained unchanged and decreased by 16% respectively. The SOM content in the 0 to 150 mm soil layer of the cover crop treatments was, with the exception of Vicia dasycarpa Ten. (grazing vetch), significantly higher than that of the mechanically-cultivated control after a period of 10 years. The SOM content in the 0 to 300 mm soil layer of Secale cereale L. v. Henog and the treatments in which the N-fixing cover crops were sown (with the exception of grazing vetch) was significantly higher than that of weedchem. The total inorganic N (TIN) concentration of the 0 to 150 mm soil layer in the BB treatments of the two Medicago species and Trifolium subterraneum L. v. Woogenellup, as measured for the 1996/97 season during full bloom of the grapevines, was significantly higher than that of the control, weedchem, and the treatments in which full-surface chemical control was applied after bud break (AB). The TIN concentration of the 0 to 600 mm soil layer in the AB treatment of a species, measured after harvest in 2002/03, tended to be higher than that of the BB treatment of that species. The applied treatments had no significant effect on the exchangeable K, Ca and Mg.